2020
DOI: 10.1108/ec-02-2020-0070
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic noise analysis and optimization for permanent magnet synchronous motor used on electric vehicles

Abstract: Purpose Electromagnetic noise of permanent magnet synchronous motor (PMSM) seriously affects the sound quality of electric vehicles (EVs). This paper aims to present a comprehensive process for the electromagnetic noise analysis and optimization of a water-cooled PMSM. Design/methodology/approach First, the noises of an eight-pole 48-slot PMSM in at speeds up to 10,000 rpm are measured. Furthermore, an electromagnetic-structural-acoustic model of the PMSM is established for multi-field coupling simulations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…T he widespread use of automobiles has exacerbated the depletion of petroleum resources. In order to solve the problems of energy shortage and environmental pollution, new energy vehicles have become the main development direction of today's automobile industry [1][2][3][4]. At present, the starter generators used for electric vehicles mainly include electroexcitation starter generator and permanent magnet starter generator.…”
Section: Introductionmentioning
confidence: 99%
“…T he widespread use of automobiles has exacerbated the depletion of petroleum resources. In order to solve the problems of energy shortage and environmental pollution, new energy vehicles have become the main development direction of today's automobile industry [1][2][3][4]. At present, the starter generators used for electric vehicles mainly include electroexcitation starter generator and permanent magnet starter generator.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional electromagnetic noise simulation mainly focuses on radial force and ignores the electromagnetic force component, which affects the simulation accuracy. In the literature [7], the radial electromagnetic force alone and the combined radial, tangential and axial electromagnetic force are analyzed. The results show that the tangential electromagnetic force has a certain degree of influence on the electromagnetic noise, and the motor stator model with radial, tangential and axial electromagnetic force is more realistic and reliable.…”
Section: Introductionmentioning
confidence: 99%
“…In [14], in order to weaken the electromagnetic force harmonics caused by tooth harmonics and thus effectively suppress the electromagnetic noise of the motor, the analytical equation of radial electromagnetic force waves of the rotor's segmented diagonal poles is derived, the suppression mechanism of segmented diagonal poles on electromagnetic noise of permanent magnet synchronous motor is analyzed, and the relationship between the number of different diagonal pole segments and the weakened tooth harmonic order is discussed. For the V-rotor permanent magnet motor for 30 kW electric vehicle drive, an optimization scheme using a new magnetic isolation bridge is proposed in the literature [15] and simulated under several characteristics, and then the feasibility and validity are verified through prototype experiments In [16], the authors used an experimental method to analyze the effect of the friction damping coefficient between the water jacket and the casing on the radiated noise of the motor, and the results showed that changing the friction coefficient between the water jacket and the casing can effectively improve the motor noise problem. In [17], the authors proposed a method for fractional-slot permanent magnet synchronous motors to inject a certain compensation current into the stator winding to cancel the radial force harmonics with the lowest modulus and thus suppress the electromagnetic vibration of fractional-slot motors.…”
Section: Introductionmentioning
confidence: 99%
“…Because the calculation of the SVPWM method before optimization needs to repeatedly transform and adjust the orthogonal coordinate system, and involves complex calculation of the trigonometric function, after the transformation of the orthogonal coordinate system, although the coordinate adjustment problem is solved, the calculation of the trigonometric function is still very complex. The SVPWM method without optimization is lengthy and has a large amount of calculation (Wang et al, 2019;. In this paper, the SVPWM calculation method in the PMSM inverter is optimized, the voltage space vector in each sector is synthesized.…”
Section: Introductionmentioning
confidence: 99%